Evidence that Ergosterol Biosynthesis Modulates Activity of the Pdr1 Transcription Factor in Candida glabrata - Bao Gia Vu; Grace Heredge Thomas; W. Scott Moye-Rowley (mBio, 2019)
ABSTRACT A crucial limitation in antifungal chemotherapy is the limited number of antifungal drugs currently available. Azole drugs represent the most commonly used chemotherapeutic, and loss of efficacy of these drugs is a major risk factor in successful treatment of a variety of fungal diseases. Candida glabrata is a pathogenic yeast that is increasingly found associated with bloodstream infections, a finding likely contributed to by its proclivity to develop azole drug resistance. C. glabrata often acquires azole resistance via gain-of-function (GOF) mutations in the transcription factor Pdr1. These GOF forms of Pdr1 drive elevated expression of target genes, including the ATP-binding cassette transporter-encoding CDR1 locus. GOF alleles of PDR1 have been extensively studied, but little is known of how Pdr1 is normally regulated. Here we test the idea that reduction of ergosterol biosynthesis (as occurs in the presence of azole drugs) might trigger activation of Pdr1 function. Using two different means of genetically inhibiting ergosterol biosynthesis, we demonstrated that Pdr1 activity and target gene expression are elevated in the absence of azole drug. Blocks at different points in the ergosterol pathway lead to Pdr1 activation as well as to induction of other genes in this pathway. Delivery of the signal from the ergosterol pathway to Pdr1 involves the transcription factor Upc2A, an ERG gene regulator. We show that Upc2A binds directly to the PDR1 and CDR1 promoters. Our studies argue for a physiological link between ergosterol biosynthesis and Pdr1-dependent gene regulation that is not restricted to efflux of azole drugs. IMPORTANCE A likely contributor to the increased incidence of non-albicans candidemias involving Candida glabrata is the ease with which this yeast acquires azole resistance, in large part due to induction of the ATP-binding cassette transporter-encoding gene CDR1. Azole drugs lead to induction of Pdr1 transactivation, with a central model being that this factor binds these drugs directly. Here we provide evidence that Pdr1 is activated without azole drugs by the use of genetic means to inhibit expression of azole drug target-encoding gene ERG11. These acute reductions in Erg11 levels lead to elevated Pdr1 activity even though no drug is present. A key transcriptional regulator of the ERG pathway, Upc2A, is shown to directly bind to the PDR1 and CDR1 promoters. We interpret these data as support for the view that Pdr1 function is responsive to ergosterol biosynthesis and suggest that this connection reveals the normal physiological circuitry in which Pdr1 participates.